SENSITIVITAS SENSOR GAS BERBASIS QUARTZ CRYSTAL MICROBALANCE TERHADAP SENYAWA ORGANIK - Rouhillah; Budi Amri (J-Innovation, 2018)
Sensors that are able to identify the type of gas are needed in the industry. One of them is a Quartz Crystal Microbalance (QCM) sensor which can produce a constant resonance frequency. In this study, we intend to determine the sensitivity of the QCM gas sensors which are coated with different polymers. QCM gas Covered with polymer sensor based QCM aim to increase the sensors ability to absorb molecules on the surface of the QCM sensor. The sensor array coated with different polymer materials will produce different frequency response output patterns for each type of gas identified. The test results showed that the QCM sensor coated with OV 17 polymer material was more sensitive by producing sensitivity of 8.4 Hz /ml alcohol, 9.96 Hz /ml 2-propanol, 35.88 Hz /ml acetone, 39.64 Hz /ml benzene.